2013
DOI: 10.1515/irsr-2013-0002
|View full text |Cite
|
Sign up to set email alerts
|

Everyday Mobility: the Normalization of China-Japan Migratory Flows and their ‘Everyday Practice’

Abstract: Chinese migrants now constitute the largest group of registered 'foreigners' in Japan, with over 600,000 documented in 2006. This is the result of an intersection between the Chinese government's drive for educational and economic success, and Japan's flexible student visa labour system. It is the product of a 'normalization' of mobility amongst young mobile Chinese. Based on 20 months fieldwork in Tokyo, Japan, I explore the ways in which the decision to move is experienced as mundane, and how it is negotiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…My research was conducted over two periods of intensive fieldwork from 2009 to 2011 and from 2014 to 2016. Through my research I found that young Chinese in Japan are torn between two national institutional frameworks, cosmopolitan and parochial desires, and feel the tensions between individual success and personal familial commitments (Coates 2013;Fong 2011;Liu-Farrer 2011. Consequently, their sense of belonging is rarely attached to a specific place, but rather shaped by projects of education, employment, and social mobility.…”
Section: The Cruel Optimism Of Mobilitymentioning
confidence: 98%
“…My research was conducted over two periods of intensive fieldwork from 2009 to 2011 and from 2014 to 2016. Through my research I found that young Chinese in Japan are torn between two national institutional frameworks, cosmopolitan and parochial desires, and feel the tensions between individual success and personal familial commitments (Coates 2013;Fong 2011;Liu-Farrer 2011. Consequently, their sense of belonging is rarely attached to a specific place, but rather shaped by projects of education, employment, and social mobility.…”
Section: The Cruel Optimism Of Mobilitymentioning
confidence: 98%
“…While the logics of this migratory flow may seem primarily economic, according to the testimonies of Chinese migrants in Japan, there are fewer contradictions between everyday economic and cultural logics than there may seem (Coates 2013). These purportedly separate logics were combined into a variety of narratives that demonstrate the blurring of the economic and cultural in the everyday.…”
Section: Personhood Mobility and The Blurring Of Cultural And Econommentioning
confidence: 99%
“…This is particularly the case for Chinese migrants in Japan, who have become the largest non‐Japanese minority in Tokyo today, making up roughly 40% of the total non‐Japanese population. From the late 1980s onwards, most came to Japan on education‐based visas and now fill vital roles in Japan's shrinking labour market (Coates ; Liu‐Farrer ; Tajima ). However, their prevalence and increasing importance in Japan has also posited them as subjects of increased surveillance and suspicion.…”
Section: Tokyo Flâneriementioning
confidence: 99%